Capability Brown, Royal Gardener (2021)
Lancelot “Capability” Brown was one of the most influential landscape designers of the eighteenth-century at a time when Britain was changing radically from an agrarian to an industrial and colonial nation, whilst Europe was periodically convulsed by war and revolution. The extent and nature of his influence are, however, fiercely debated. Brown worked at hundreds of important sites across England and his name became synonymous with the “English Garden” style which was copied across Northern Europe and entranced Catherine the Great, who remodelled her landscapes in St Petersburg to reflect the new style. He was fêted in his time, and recognised by the Crown, but Brown’s style was readily copied over his later life and particularly after his death. Arguably, this ubiquity led to the denigration of his achievements and even his character, particularly by the agents of the Picturesque. The lack of any personal primary material from Brown - forcing scholars to rely on his landscapes, contracts and bank accounts - has hindered attempts to provide a rounded and credible account of the man and his works. However, by exploring his team of associates and his role as Royal Gardener, new light can be thrown on the man, his landscapes and his landscape legacy. Bringing together a number of perspectives from across Northern Europe, Capability Brown, Royal Gardener explores the lasting international impact of Brown. With Brown’s position as Royal Gardener at its heart, this book explores for the first time his business methods, working methods and European influence. It assesses how, crucially, Brown’s work practices placed him within the world of nurserymen and landscape designers, and how his business practices and long term relationships with draughtsmen and designers allowed him to manage a huge number of projects and a substantial financial turnover. This, in turn, allowed him to work in a way that promoted and advanced his style of landscape. Edited by Professor Jonathan Finch (University of York) and Dr Jan Woudstra (University of Sheffield), and with a varied range of engaging contributors drawn internationally from archaeology, art history, history and landscape architecture, Capability Brown, Royal Gardener weaves together strands from across a broad range of disciplinary interests. It makes an important contribution to the scholarly discussion of Brown’s work, the work of his collaborators, and legacy in the UK and across Northern Europe. Relevant to students and academics at all levels, this volume throws new light on Capability Brown and his impact on the business of place-making in Northern Europe.